2016
DOI: 10.1111/epi.13344
|View full text |Cite
|
Sign up to set email alerts
|

De novo GABRA1 mutations in Ohtahara and West syndromes

Abstract: Summary Objective GABRA1 mutations have been identified in patients with familial juvenile myoclonic epilepsy, sporadic childhood absence epilepsy, and idiopathic familial generalized epilepsy. In addition, de novo GABRA1 mutations were recently reported in a patient with infantile spasms and four patients with Dravet syndrome. Those reports suggest that GABRA1 mutations are associated with infantile epilepsy including early onset epileptic encephalopathies. In this study, we searched for GABRA1 mutations in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 40 publications
8
94
0
Order By: Relevance
“…Mutations of this gene are known to be associated with Dravet syndrome 10 and with early infantile epileptic encephalopathy. 12 However, while his phenotype combines some of the key features of the syndrome, there are important aberrations, regarding the age at onset, type of seizures, EEG findings, and response to therapy. Therefore, he can be considered as an atypical Dravet syndrome phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of this gene are known to be associated with Dravet syndrome 10 and with early infantile epileptic encephalopathy. 12 However, while his phenotype combines some of the key features of the syndrome, there are important aberrations, regarding the age at onset, type of seizures, EEG findings, and response to therapy. Therefore, he can be considered as an atypical Dravet syndrome phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…49 Gamma-aminobutyric acid-related genes Mutations in genes encoding subunits of the gammaaminobutyric acid (GABA) type A receptor are increasingly recognized in the epilepsy-dyskinesia spectrum. 50 Recently a de novo GABRA2 mutation was found in a patient with DEE, who also had severe hypotonia, and continuous choreiform movements. Reported Figure 1: Pathophysiology of genetic epilepsy-dyskinesia phenotypes.…”
Section: Sodium Channel Genesmentioning
confidence: 99%
“…The -aminobutyric acid (type A) receptor (GABA A R) is emerging as a major causal agent in some forms of genetic epilepsy. Heritable mutations to the GABA A R , ,  and  subunits have been identified in family pedigrees of epilepsy (6) and new mutations continue to be identified (7,8). Studies of thalamo-cortical connections of the brain have demonstrated that epileptic states are preceded by the synchronisation of excitatory activity in neuronal populations.…”
Section: Introductionmentioning
confidence: 99%